Psychoanalytic Underpinnings of Socially-Shared Normativity - Forrester, Michael (Frontiers in Psychology, 2019)
Alongside social anthropology and discursive psychology, conversation analysis has highlighted ways in which cultural forms of perceiving and acting in the world are primarily rooted in socially shared normativity. However, when consideration turns to the origins and purposes of human affect and emotion, conversation analysis appears to face particular difficulties that arise from the over-arching focus on sense-making practices. This paper considers the proposal that psychoanalytic thinking might inform our understanding of how socially shared normativity emerges during infancy and early childhood. First, a framework is sketched out that highlights the fact that from the beginning an infant’s earliest experience is bound up with those practices and social actions that make up what conversation analyst’s call members’ methods. Second, comparisons are drawn between conversation analysis and psychoanalytic accounts of early experience for infants during the first years of life. Discussion then moves to the Kleinian notion of object relations, and the concept of projective identification. Essentially, this is a theoretical account of how ‘what-was-once-one’ (the mother-infant unit) differentiates resulting in the gradual emergence of the ‘individuated being’. What is often glossed over in this account is the discursively embedded nature of projective identification; a process that is itself interdependent with the embodiment that makes up the infant’s lived engagement with the world. Whatever might constitute consciousness emerges from somatic, embodied, material-physical, tactile/affective experience – that is, a fundamentally social milieu. This raises the question of how transformation (i.e., from the social to the individual) occurs. One answer may be Winnicott’s idea of the transitional space, where the ‘good-enough’ parent is said to be somebody who can ‘contain’ both negative and positive identifications coming from the infant, transform and re-project such identifications, but in modified from. In this way the infant begins to recognise/experience what it is they are ‘feeling’. Such projective identifications are conveyed within and through the prevailing discourses that constitute all social practices. Concluding comments note that conversation analysis may find in psychoanalytic thinking a framework for understanding the interdependence between affect and action, as in psychoanalytic thought we find a thoroughly relational conception of human nature.